Consumption of junk foods by school-aged children in rural Himachal Pradesh, India - Aakriti Gupta; Umesh Kapil; Gajendra Singh (Wolters Kluwer Medknow Publications, 2018)
There has been an increase in the consumption of junk food (JF) among school-aged children (SAC) possibly leading to obesity and diet-related diseases among them. We do not have evidence on consumption of JF in rural areas; hence, we conducted a study to assess the consumption of JF by SAC in rural, Himachal Pradesh. A total of 425 children in the age group of 12-18 years studying in 30 government schools (clusters) were included. The clusters were selected using population proportionate to size sampling methodology. We found high prevalence (36%) of consumption of JF among SAC during the last 24 h. Efforts should be taken to reduce the consumption of JF by promotion of healthy dietary habits and educating children about the ill effects of JF.